An immersion and invariance-based speed observer for visual servoing. (15th October 2012) - Yang, Bo; Li, Hui-Guang; Sha, Xiao-Peng; Shao, Nuan
In visual servoing, joint speeds of the robot are required for feedback control. However, most robots are not equipped with the angular velocity sensors. This paper deals with a speed observer for a visual servoing system based on the immersion and invariance (I&I) technique. The visual servoing system, a new binocular stereo visual model (BSVM) is considered, which 3-dimension image information is obtained directly, that we need not to estimate the depth information. We have considered the visual servoing system that contained the non-linear robot dynamics, an image-based controller and a speed observer. It will make the stabilisation analysis of the closed-loop system very difficult. A controller is designed so that the robot visual servoing system is transformed into a port-controlled Hamiltonian (PCH) system. It will simplify the stabilisation analysis. For the PCH system, firstly, a speed observer is designed by the technical of I&I. Secondly, a visual servo controller is designed to satisfy the visual servoing performance. Simulation experiments illustrate the theory and show the effectiveness of the proposed designs.